The Interaction of Obesity and Reproductive Function in Adolescents - Elliott, Victoria; Waldrop, Stephanie W.; Wiromrat, Pattara; Carreau, Anne-Marie; Green, Melanie Cree (Seminars in Reproductive Medicine, 2022)
Obesity is increasing worldwide, including in pediatrics. Adequate nutrition is required for initiation of menses, and there is a clear secular trend toward earlier pubertal onset and menarche in females in countries around the globe. Similar findings of earlier pubertal start are suggested in males. However, as individuals and populations have crossed into over-nutritional states including overweight and obesity, the effect of excess weight on disrupting reproductive function has become apparent. Hypothalamic hypogonadism and polycystic ovary syndrome are two conditions where reproductive function appears to directly relate to excess weight. Clinical findings in individuals with certain polygenic and monogenic obesity syndromes, which also have reproductive disruptions, have helped elucidate neurologic pathways that are common to both. Clinical endocrinopathies such as hypothyroidism or panhypopituitarism also aide in the understanding of the role of the endocrine system in weight gain. Understanding the intersection of obesity and reproductive function may lead to future therapies which can treat both conditions.
Keywords: obesity; adolescence; reproductive disturbances